Signal processing of heart signals for the quantification of non-deterministic events - Millette, Veronique (University of Ottawa (Canada), 2010)
The issue of cavitation in mechanical heart valve (MHV) patients was first recognized when damaged mechanical heart valves were observed. Cavitation bubble implosion can cause mechanical damage to the valve structure and blood elements, when it occurs near the surface of the MHV. Some methods have been suggested to quantify the level of cavitation present in MHV patients. Two algorithms from the literature were selected for implementation and comparison. These algorithms were selected as they have been previously proposed and implemented for in vivo heart signals. In this thesis, a rigorous closed-form mathematical analysis of the algorithms is presented with the aim of improving robustness, reliability and accuracy. Improvements are made to the selected algorithms, including a new improved segmentation algorithm, alignment of the S1 and S2 peaks in the signal, and the implementation of the Short-Time Fourier Transform to study the time evolution of the energy in the signal. In vitro measurements were made using a left-heart simulator to test the new improved algorithm. The improvements result in better heart beat alignment and better detection and measurement of the random events in the heart signals, so that they may provide a method to analyze cavitation in MHV patients. The use of the Short-Time Fourier Transform allows the examination of the random events in both time and frequency allowing for further investigation and interpretation of the signal. Cavitation results from the physiologically realistic left-heart simulator indicate that cavitation may not occur under normal physiological heart conditions.
Keywords: Engineering, Biomedical.